Coronavirus Disease 2019-Related Fulminant Idiopathic Intracranial Hypertension - Çalışkan, Burcu; Canbal, Abdullah; Güven, Ahmet Sami; Bitirgen, Gülfidan; Erdi, Mehmet Fatih; Çaksen, Hüseyin (Journal of Pediatric Neurology, 2023)
Idiopathic intracranial hypertension or pseudotumor cerebri syndrome (PTCS) is defined as an increase in intracranial pressure (ICP) without an identifiable and/or structural cause or abnormal cerebrospinal fluid content. The most common symptoms of PTCS include headache, vomiting, pulsatile tinnitus, blurred vision, and diplopia. In 2 to 3% of PTCS patients, severe and rapidly progressive vision loss may develop within 1 month since symptoms begin; this clinical condition is usually defined as fulminant idiopathic intracranial hypertension (FIIH). This study presented a patient admitted to the hospital with headache and blurred vision, who also had high severe acute respiratory syndrome coronavirus 2 infections total antibody level and was treated with a lumboperitoneal shunt due to medical treatment-resistant increased ICP. We also reviewed similar cases previously reported in the literature. To the best of our knowledge, no children affected with coronavirus 2019 related to FIIH and requiring surgical treatment have been yet reported in the literature.
Keywords: COVID-19; fulminant idiopathic intracranial hypertension; pseudotumor cerebri